Three men and a little lady - Selleck, Tom, 1945-; Guttenberg, Steve; Danson, Ted, 1947-; Serreau, Coline ([S.l.] : Touchstone Home Video, 1991)
Three carefree bachelors are sharing the upbringing of Mary, an adorably curious 5-year-old. Mary's mother accepts a marriage proposal, which means relocation in England, and she takes Mary with her. The ex-dads quickly discover how empty life is without their little lady, and go to outrageous lengths to get her back.
Based on "Trois Hommes Et Un Couffin" written by Coline Serreau.
Videodisc release of the motion picture.
"This film has been modified from its original version. It has been formatted to fit your TV."--Container.
For specific features see interactive menu.
Tom Selleck, Steve Guttenberg, Ted Danson, Nancy Travis.
DVD; Dolby Digital surround sound.
Keywords: Fathers and daughters; Bachelors; Child rearing; Feature films; Comedy films; Video recordings for the hearing impaired